The prevalence of and attitudes toward oligomenorrhea and amenorrhea in Division I female athlete - Myrick, K.; Feinn, R.; Harkins, M.; Eberman, L. E. (International Journal of Athletic Therapy & Training, 2012)
The article discusses a cross-sectional study conducted to determine the prevalence of and attitudes toward oligomenorrhea and amenorrhea among Division I female athletes of National Collegiate Athletic Association. Topics include determination of the perceptions of missed menstrual cycles, categorization of sports into two groups which include lean and non-lean sports; and characteristics of menstrual cycle. The study suggests for better education of coaches, athletes and athletic trainers.